Manajemen Pembiayaan Dalam Meningkatkan Mutu Layanan Pendidikan di SMK Al-Huda Kota Kediri - Weny, Siska Yulia; Dhari, Arifah Dwi Wahyu Wulan (JoIEM (Journal of Islamic Education Management), 2024)
The purpose of this study is to find out how to plan financing management, implement financing management, evaluate financing management and understand the role of financing management in improving the quality of educational services. This study used a qualitative approach using a type of descriptive research. Data collection techniques carried out are by means of interviews, observation, and documentation. Data analysis techniques with data reduction stages, data presentation, and conclusions. The results of this study show that: 1) financing management is planned at the beginning of the new learning year by making proposals for budget activities called the School Budget Activity Plan (RKAS). 2) The implementation of financing management activities is divided into two, namely revenue and expenditure. 3) The evaluation process of education financing management is carried out as evidenced by a spending note. The supervision process is carried out through the SIPLAH application by the school operator and supervised by the Foundation. 4) The role of financing management is as a source to provide services for school residents and for learners to meet needs.